Pengembangan E-Modul Untuk Kompetensi Dasar Menerapkan Plain Cake Bagi Siswa SMKN 1 Cerme Gresik - Ery Widar Ariyanto; Sri Handajani; Any Sutiadiningsih; Andika Kuncoro Widagdo (CV. Aksara Global, 2023)
The aims of this study were to find out: 1) e-module eligibility for basic competence in applying plain cake in terms of material and media, and 2) e-module feasibility for basic competency in applying plain cake from the user's point of view.The development model in this study is ADDIE (Analysis, Design, Development, Implementation, Evaluation) which is carried out until the third stage of Development. Subjects for the feasibility of the e- module from the user's point of view were 23 students of SMKN 1 Cerme Gresik in the Culinary Expertise Field. The feasibility assessment of the e-module in terms of material and media was carried out by material experts and media experts, each consisting of 3 material experts and 3 media experts. The data collection instruments used in this study were questionnaires, which consisted of: 1) expert feasibility assessment questionnaires, and 2) user feasibility assessment questionnaires. The questionnaire will be assessed using a Likert scale with 5 rating scales, then will be grouped based on Likert scale score interpretation criteria. The data analysis technique used in this study is descriptive quantitative which will explain the results of the assessment by percentage. The results of this study are: 1) e-module feasibility in terms of material and media is very feasible (91.3% and 91.4%), 2) e-module feasibility from the user's point of view is very feasible (81.8%)